KONSTRUKSI BERITA PANAMA PAPERS DI TEMPO.CO - Bambang Gustiawan; Subhan Afifi; M. Edy Susilo (Jurnal Paradigma, 2017)
Lackage of financial data case in Panama or populary called Panama Papers is being a serious issue in the world, as well as in indonesia, because it impicates many important people of indonesia. All of mass media that report about this issue with a their own perspectives and constructed it into a news frame. This research reveals how Panama Papers are framed into the Tempo.co news. Data Collection technique and data analysis used in this research is framing analysis model developed by Zhongdang Pan and Gerald M. Kosicki which is divided into four structures, that is syntax (how journalists make facts), scripts (how journalists tell the facts), thematic (the way journalists write facts) and rhetorical (the way journalists emphasize facts). Objects studied in this study are news from the news portal Tempo.co from April to October 2016 edition which write about Panama Papers. The results of the study obtained three important conclusions, First, Tempo.co has a view to the public and the public interest, seen from the tendency of news that criticizes the government. Second, the construction has built by the Tempo.co indentified by the position of source of the news. The source of the news who representing media frames are placed more dominant in the opening of paragraphs and vice versa. Third, as an independent media and free from all pressure, Tempo.co consistently constructs Panama Papers with a point of view criticizing the government’s performance for the better. It is in line with the mission of Tempo.co as a free and responsible press